Tinjauan Perkembangan Teknologi Membran dalam Pemisahan Gas CO₂ dari CH₄ - Rafi Indratama (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Global CO₂ emissions exceeding 30 billion tons annually significantly contribute to global warming, including in natural gas, biogas, and landfill gas streams containing CH₄. High CO₂ content lowers CH₄’s calorific value, requiring efficient separation technology. Gas membranes offer an energy-efficient, low-cost, and simple alternative to conventional methods. This study reviews advancements in CO₂/CH₄ separation membranes, focusing on material innovations and performance. A systematic literature review was conducted following PRISMA guidelines, covering international publications (2010–2025) with relevant keywords. Data were analyzed qualitatively and quantitatively by membrane type, material, separation mechanism, and performance parameters such as permeability (PCO₂) and CO₂/CH₄ selectivity. Results show a publication surge after 2015, driven by developments in high-free-volume polymers (PIMs), carbon molecular sieves (CMS), zeolite-based inorganic membranes, mixed-matrix membranes (MMMs), and 2D materials like graphene and MOFs. Some materials exceeded the Robeson limit, achieving PCO₂ in the tens of thousands of Barrer with selectivity >100. Remaining challenges include plasticization, long-term stability, production costs, and scalability.